1983
DOI: 10.1111/j.1471-0528.1983.tb08943.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a factor blocking a cellular cytotoxicity reaction in the serum of women with recurrent abortions

Abstract: Summary. The serum of pregnant women contains a non‐specific immuno‐suppressive factor able to block an in vitro cellular cytotoxicity reaction. This activity increases during the first trimester and persists for 3 months after delivery. The factor is active in dilution. Ten women who had recurrent abortions were typed for HLA antigens and were found to share several antigens with their husband. In all these women, the‘blocking factor’was absent from their serum. The absence of the‘blocking factor’could be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Therefore, P4 is different from normal im munosuppressive protein [ 17]; C-reactive pro tein appears only during the last trimester [18]; pregnancy proteins like PAPP-A [19] possess a subunit (200,000 daltons) but dis appear quickly after delivery and a specific immunserum doesn't absorb P4 activity. We have shown that P4 is not a placental prod uct; it appears in women taking oral contra ceptives [12], The important point is that P4 is absent from the serum of women with recurrent abortions [10]. It is suggested that P4 is nec essary for the maintenance of fetal allograft.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, P4 is different from normal im munosuppressive protein [ 17]; C-reactive pro tein appears only during the last trimester [18]; pregnancy proteins like PAPP-A [19] possess a subunit (200,000 daltons) but dis appear quickly after delivery and a specific immunserum doesn't absorb P4 activity. We have shown that P4 is not a placental prod uct; it appears in women taking oral contra ceptives [12], The important point is that P4 is absent from the serum of women with recurrent abortions [10]. It is suggested that P4 is nec essary for the maintenance of fetal allograft.…”
Section: Resultsmentioning
confidence: 84%
“…We have brought to light the appearance during pregnancy of a factor able to inhibit nonspecifically a cellular cytotoxicity reac tion in vitro [10]. The sera of women with repeated spontaneous abortions were free from this protein [11].…”
mentioning
confidence: 99%
“…The technique used [10][11][12] makes it possible to measure the inhibitory' activity of different sera on a cytotoxicity reaction between in vitro sensibilized lymphocytes against allogenic lymphocytes from an HLA-incompatible donor. The degree of cytotoxicity was measured scoring the percentage of dead cells, using trypan blue dye exclusion.…”
Section: Cellular Cytotoxicity In Vitromentioning
confidence: 99%
“…[5] revealed the same immunosuppressive properties of glycopro teins in the serum of pregnant women, in those taking contraceptives and also in the sera of patients affected by malignant tu mors. A previous study [10], using the cellu lar cytotoxicity reaction in vitro, brought to light, in an original way, the appearance dur ing pregnancy of an immunosuppressive fac tor. This nonspecific protein seems to be dif ferent from those previously described by different authors.…”
Section: Introductionmentioning
confidence: 99%
“…Other criteria include the lack of paternal HLA lymphocytotoxic antibodies [8][9][10] or the lack of mixed lymphocytic reaction (MLR) blocking antibodies [11][12][13]. These antibodies are commonly present in the sera of normal multiparous women but found to be lacking in the sera of recurrently aborting women [14][15][16][17][18][19][20].…”
mentioning
confidence: 99%